Evaluation and improvement of ETSI ITS Contention-Based Forwarding (CBF) of warning messages in highway scenarios - Amador, Óscar; Urueña, Manuel; Calderón, María; Soto, Ignacio (Vehicular communications, 2022)
This paper evaluates the performance of the ETSI Contention-Based Forwarding (CBF) GeoNetworking protocol for distributing warning messages in highway scenarios, including its interaction with the Decentralized Congestion Control (DCC) mechanism. Several shortcomings of the standard ETSI CBF algorithm are identified, and we propose different solutions to these problems, which are able to reduce the number of transmissions by an order of magnitude, while reducing the message end-to-end delay and providing a reliability close to 100% in a large area of interest. (C) 2022 Elsevier Inc. All rights reserved.
Keywords: ETSI Intelligent Transport Systems (ITS); Decentralized Environmental Notification; Message (DENM); Contention-Based Forwarding (CBF); Decentralized Congestion Control (DCC); Duplicate Packet Detection (DPD); JCR; Scopus